Interfacing triple bottom line sustainability and metropolitan governance: An empirical exploration of stakeholder value co-creation and conflict - Chen, Shaohan; Kamarudin, Khairul Manami (Elsevier, 2024)
The importance of metropolitan governance and stakeholder collaboration in sustainable urban development (SUD) is well recognized. However, collaboration among stakeholders is dynamic, and the relationship between metropolitan governance and stakeholder dynamics, including value co-creation and conflict, remains underexplored. This study aims to address this gap by examining the causal relationships among metropolitan governance, stakeholder value co-creation and conflict through the lens of the triple bottom line (TBL) of sustainability. Using a questionnaire survey, this study collected 467 valid responses through a combination of probability and quota sampling and analyzed the data using Structural Equation Modeling. The results indicated that stakeholder value co-creation is positively influenced by TBL dimensions and metropolitan governance, thereby simultaneously promoting SUD and generating potential conflicts that constrain SUD. The study further evaluated the effectiveness of stakeholder value co-creation as a mediating variable and found that it has a unique suppressing effect on the relationship between environmental sustainability and conflict. The findings suggested that environmental sustainability-driven governance initiatives are crucial to containing conflict and fostering value co-creation among stakeholders. Theoretically, this study enriches the discourse on SUD literature by quantifying the interactions between TBL, metropolitan governance and stakeholder dynamics. Practically, it provides certain implications for relevant practitioners by proposing an argument that governance initiatives can be aligned with the shifting priorities toward environmental sustainability. © 2024